2018
DOI: 10.1007/s10585-018-9898-6
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastasis in melanoma: a debate on the significance of nodal metastases, conditional survival analysis and clinical trials

Abstract: While there is no doubt that regional lymph node metastases are an enormously important factor in melanoma staging and treatment, the biology behind this significance and its precise implications for treatment planning have been a leading controversy in melanoma and other solid tumors for over a century. Recent clinical data, including data from prospective randomized clinical trials have refined our understanding of the process of nodal metastases and the advantages and disadvantages of different clinical man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…At present, performing a SLNB is mostly advised because of the impact on further adjuvant systemic (immune)therapy or trial participation. Moreover, the present data indicate that performing a SLNB in these patients has also some therapeutic effect, supporting in some way the incubator hypothesis [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At present, performing a SLNB is mostly advised because of the impact on further adjuvant systemic (immune)therapy or trial participation. Moreover, the present data indicate that performing a SLNB in these patients has also some therapeutic effect, supporting in some way the incubator hypothesis [7].…”
Section: Discussionsupporting
confidence: 88%
“…The discussion on this matter can be summarized as between two hypothesis camps: those who consider lymph nodes to be incubators for sequential “orderly progression” of the disease and those who consider this only as marker or indicator of the melanoma’s metastatic potential [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLNB has important prognostic value in cutaneous melanoma . The Multicenter Selective Lymphadenectomy Trial (MSLT)‐I demonstrated that SLN status is an important predictor for recurrence and death from melanoma in intermediate‐thickness cases (1‐4 mm) .…”
Section: Discussionmentioning
confidence: 99%
“…SLNB has important prognostic value in cutaneous melanoma. [8][9][10][11] The Multicenter Selective Lymphadenectomy Trial (MSLT)-I demonstrated that SLN status is an important predictor for recurrence and Additional studies have concluded that SLN status is also prognostic in cases of thick ( > 4 mm) melanoma. [13][14][15][16][17] This is of particular importance in ALM, in which patients typically have a delayed presentation with thicker melanomas, and a quarter of all nodal-staged patients with ALM will have a positive SLN.…”
Section: Discussionmentioning
confidence: 99%
“…Although the true value of completion lymph node dissection in patients with positive SLN remains controversial, the accurate staging of lymph nodes is an important prognostic factor for patients with melanoma . Moreover, not all melanocytic cells found within a draining lymph node basin indicate aggressive biologic behavior, and nodal nevus could be mistaken for metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%